THE EFFECT OF INCREASED BLOOD PRESSURE ON THE DECREASING QUALITY OF LIFE OF ELDERLY PEOPLE WITH HYPERTENSION - Istianna Nurhidayati; Arlina Dhian Sulistyowati; Sri Sat Titi Hamranani; Sandra Risa Paramita (Jurnal Keperawatan Respati Yogyakarta, 2023)
Hypertension is one of the most important risk factors for cardiovascular disease, especially in the elderly. Recent data show that almost half of the patients with hypertension and one-third of the elderly with comorbidities were non-adherent to treatment. This study aims to assess the relationship between blood pressure and the quality of life (QoL) of the elderly with hypertension. This was a quantitative correlation study carried out with a cross-sectional approach and an analytic study. The sampling technique utilized was simple random sampling. This study involved 104 elderly patients with hypertension. The WHOQOL-OLD questionnaire and a blood pressure measuring device were used to collect the data. The data were then analyzed using Kendall Tau (p-value 0.000 <0.05). The results showed that 74% of the elderly had uncontrolled blood pressure and 60.6% had a low QoL category. The results of Kendal's analysis showed a relationship between blood pressure and quality of life for the elderly with hypertension (p=0.000; r= -734). In conclusion, there was a relationship between blood pressure and the quality of life of the elderly with hypertension. Moreover, an increase in blood pressure would reduce the QoL level of the elderly.